Osteocyte staining with rhodamine in osteonecrosis and osteoarthritis of the femoral head. Issue 12 (1st October 2019) - Rony, Louis; Perrot, Rodolphe; Hubert, Laurent; Chappard, Daniel
Abstract: Death of osteocytes is synonymous of bone death. Aseptic osteonecrosis of the femoral head is a lesion characterized by the death of osteocytes occurring after major vascular changes. The evolution may lead to hip osteoarthritis, which requires total hip arthroplasty in most cases. Evolution of aseptic osteonecrosis in four radiological stages is well known. We analyzed 24 femoral heads from patients with osteonecrosis or osteoarthritis, retrieved at the time of surgery for a hip arthroplasty. The aim of the study was to clearly identify the necrotic bone from the living bone in the histological samples. The femoral heads were sawed, and a large sample was harvested in the superior zone; it was stained en‐bloc with rhodamine dissolved in formalin to make the osteocytes fluorescent under UV light microscopy. Undecalcified sections, 7 μm thick, were obtained on a heavy‐duty microtome. A micrographic analysis using two UV excitation wavelengths visualized the living osteocytes (in green) and the bone matrix (in blue). A simple method to prepare combined images is described. In addition, the blocks can be analyzed by confocal microscopy to visualize more details. It is possible to identify at low magnification the osteocytes within the bone matrix and the osteonecrotic areas where osteocytes have disappeared. Identification of osteocytes showed that newly formed bone packets are laid on dead trabeculae in patients with aseptic osteonecrosis or with osteoarthritis. In the osteosclerotic areas, the enlarged trabeculae have a dead central core surrounded by recently apposed bone structure units. Abstract : Osteocytes are embedded in the bone matrix. When osteocytes disappear, the bone area is considered dead. Osteonecrosis is a disease characterized by the death of osteocytes. Rhodamine allows their analysis by fluorescence and confocal microscopy.